siRNA Design Methods and Protocols - Taxman, Debra J.; Taxman, Debra J. (Methods in Molecular Biology, 2013)
The discovery of RNA interference (RNAi) as a methodology for gene silencing has revolutionized biological research, providing an invaluable avenue for therapeutics, and small interfering RNA (siRNA) is the most common strategy utilized for enacting RNAi.  siRNA Design: Methods and Protocols offers expertly crafted guidelines and protocols for the selection of siRNA targeting sequences, for the strategic incorporation of chemical modifications, and for advantageous structural modifications to the classic siRNA design. Protocols are provided for using endogenous cellular machinery to produce siRNA from optimized precursor short hairpin RNA (shRNA) and artificial microRNA (amiRNA) molecules. Strategies are also described for specific applications such as immunostimulatory siRNA that may provide therapeutic benefit against viral infections in mammals, the simultaneous targeting of multiple siRNAs, and siRNA-mediated crop virus resistance.  The design of RNAi for gene silencing in embryonic, invertebrate, and plant systems requires a variety of unique approaches, several of which are described towards the end of this volume.  Written for the highly successful Methods in Molecular Biology™ series, this work contains the kind of detailed description and implementation advice that guarantees successful results.   Authoritative and easy to use, siRNA Design: Methods and Protocols will provide researchers, educators, clinicians, and biotech specialists with a broad understanding of the issues in RNAi and how they can be overcome strategically through design.